Strong Dependence of U.S. Summertime Air Quality on the Decadal Variability of Atlantic Sea Surface Temperatures. Issue 24 (26th December 2017) - Shen, Lu; Mickley, Loretta J.; Leibensperger, Eric M.; Li, Mingwei
Abstract: We find that summertime air quality in the eastern U.S. displays strong dependence on North Atlantic sea surface temperatures, resulting from large‐scale ocean‐atmosphere interactions. Using observations, reanalysis data sets, and climate model simulations, we further identify a multidecadal variability in surface air quality driven by the Atlantic Multidecadal Oscillation (AMO). In one‐half cycle ( 35 years) of the AMO from cold to warm phase, summertime maximum daily 8 h ozone concentrations increase by 1–4 ppbv and PM2.5 concentrations increase by 0.3–1.0 μg m −3 over much of the east. These air quality changes are related to warmer, drier, and more stagnant weather in the AMO warm phase, together with anomalous circulation patterns at the surface and aloft. If the AMO shifts to the cold phase in future years, it could partly offset the climate penalty on U.S. air quality brought by global warming, an effect which should be considered in long‐term air quality planning. Key Points: This study quantifies for the first time the multidecadal influence of sea surface temperature on variability in U.S. air quality Summertime air quality in the eastern United States degrades in the warm phase of the Atlantic Multidecadal Oscillation (AMO) An AMO shift to the cold phase in future years could partly offset the climate penalty on U.S. air quality brought by global warming